2014
DOI: 10.1177/0218492314531138
|View full text |Cite
|
Sign up to set email alerts
|

Acute subdural hematoma after aortic surgery: A retrospective comparative study

Abstract: This retrospective study demonstrated that the subdural hematoma group received fewer units of platelets, thus it appears to be important to give platelets appropriately. Strict flow regulation or avoidance of retrograde cerebral perfusion is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The hemorrhagic disorder associated with Heyde syndrome would enhance massive bleeding which resulted in the formation of the large subdural hematoma with severe midline shift. Subdural hematoma following open-heart surgery is sometimes life-threatening, but early diagnosis and prompt treatment may lead to neurological recovery in many cases [7–10]. Especially in our patient, severe hemorrhagic tendency enhanced by Heyde syndrome led to large subdural hematoma and irreversible neurological deterioration.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The hemorrhagic disorder associated with Heyde syndrome would enhance massive bleeding which resulted in the formation of the large subdural hematoma with severe midline shift. Subdural hematoma following open-heart surgery is sometimes life-threatening, but early diagnosis and prompt treatment may lead to neurological recovery in many cases [7–10]. Especially in our patient, severe hemorrhagic tendency enhanced by Heyde syndrome led to large subdural hematoma and irreversible neurological deterioration.…”
Section: Discussionmentioning
confidence: 79%
“…Intracranial hemorrhagic events occurring following open-heart surgery are uncommon but may prove devastating due to enhanced bleeding tendency caused by heparin administration, hypothermia, and postoperative anticoagulation therapy [7–10]. Of these, the incidence of subdural hematoma after open-heart surgery was 0.1% [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several causes of SDH have been postulated. [11][12][13] SDH after cardiac and aortic surgeries have been reported. 11,12 In a series of patients undergoing aortic surgery, 15% were found to have symptomatic SDH, all of which were managed conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…2,9 Interestingly, they cite another study that found increased incidence of SDH in aortic surgery to be associated with decreased administration of platelet volume. 10 There are likely other reasons of which we may be unaware. We would caution against jumping to conclusions and preemptively attributing the increased incidence of SDH to inexperience, because there is no evidence that the duration of circulatory arrest is a consistent metric for this.…”
Section: Experience Does Matter For Pulmonary Endarterectomy Surgery mentioning
confidence: 99%